TOKOH AYAH DALAM AL-QURAN DAN KETERLIBATANNYA DALAM PEMBINAAN ANAK - Rahmi Rahmi (Universitas Islam Negeri Imam Bonjol Padang, 2015)
The coaching and education who first received by the children, is from their parents. The role of parents both father and mother had the most important position in the formation of the child's personality. An explanation of how the role of a mother in children's nurturing and educating of them, have been a lot of exposed by some literature. An explanation about the role of fathers, especially in the development and education of children has not been revealed. This article will review in depth how the urgency of the father's role in nurturing and educating children on Al Quran, whose the father figure in the al-Quran, and how any involvement of fathers according to the Qur'an.